A rare earth element-doped laminated piezoelectric sensing material and a preparation method thereof
Patent Information
- Application Number
- CN202510099249.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-01-22
AI Technical Summary
[0004]本发明的目的是解决现有压电材料在高温时压电系数急剧降低的问题
[0027] This invention provides a rare-earth element-doped multilayer piezoelectric sensing material and its preparation method to improve the sensitivity and reliability of partial discharge sensors in power equipment, thereby enhancing the accuracy of partial discharge fault detection in power equipment such as transformers. This invention employs an improved two-step solid-state reaction method. First, MgNb₂O₆ and PbTiO₄ precursors are pre-calcined. After mixing, 1.4 wt.% of Gd₂O₃ and Y₂O₃ rare-earth oxides are added respectively. A multilayer piezoelectric block is obtained by cold isostatic pressing. Sintering and polishing yield a piezoelectric sensing material with high piezoelectric coefficient and stable temperature performance. This invention also provides a general and direct method for developing high-sensitivity and high-reliability ultrasonic sensors, offering advantages such as low cost, ease of operation, and predictable results.
Smart Images

Figure CN120081666B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of piezoelectric materials, specifically relating to a rare earth element-doped multilayer piezoelectric sensing material and its preparation method. Background Technology
[0002] Ultrasonic partial discharge detection technology is currently the mainstream partial discharge detection technology. Its advantages include wide applicability, applicable to monitoring various equipment in power equipment and substation spaces such as GIS, transformers, switchgear, and overhead lines; ability to locate partial discharges; low site requirements, immunity to electromagnetic interference, allowing testing to be completed with the sensor close to the equipment casing or even without contact; no impact on equipment operation; small size and narrow bandwidth, suitable for online monitoring. Therefore, ultrasonic detection technology is widely used in power grids. With the increasing demand for comprehensive equipment sensing and defect early warning in power grid digitalization, ultrasonic sensors will be widely used in the online monitoring and defect location of power equipment such as transformers. This will further increase the application volume, placing higher demands on the sensitivity and reliability of ultrasonic sensors. This requires the core piezoelectric sensing material of the sensor to possess a high piezoelectric coefficient and good temperature stability.
[0003] Lead magnesium niobate-lead titanate (Pb(Mg) 1 / 3 Nb 2 / 3 PMN-PT (PbTiO3-PbO3, hereinafter referred to as PMN-PT) binary ceramics are a rapidly developing type of relaxor ferroelectric material in recent years. They possess characteristics such as high dielectric constant, high voltage, and low sintering temperature, and have broad application prospects in micro-displacement actuators, ultrasonic transducers, and accelerometers. Existing research indicates that adding rare-earth dopants to PMN-PT is considered an effective method to enhance its local structural heterogeneity. In 2018, Xi'an Jiaotong University incorporated 2.5 mol% Sm3+ into (1-x)PMN-xPT ceramics, altering the local structure of lead-based perovskite ferroelectrics and obtaining PMN-PT piezoelectric ceramic materials with a piezoelectric coefficient as high as 1500 pC / N and a dielectric constant exceeding 13000. However, using Sm2O3 as the dopant element is expensive. Furthermore, the Curie temperature of Sm-doped PMN-PTs is mostly at 60℃ or even lower, while the surface temperature of some power equipment or the ambient temperature can reach as high as 60℃. This causes the PMN-PT material to depolarize to the paraelectric phase and drastically reduce the piezoelectric coefficient, leading to a significant decrease in sensor sensitivity and poor reliability. Therefore, it is unsuitable for large-scale production and application in the field of power equipment monitoring. In addition, the traditional niobate process for preparing rare-earth element-doped (1-x)PMN-xPT ceramics easily induces the formation of a large amount of pyrochlore phase, making it difficult to obtain a pure perovskite structure, thus significantly reducing the piezoelectric and dielectric properties of the ceramic. Summary of the Invention
[0004] The purpose of this invention is to solve the problem that the piezoelectric coefficient of existing piezoelectric materials decreases sharply at high temperatures.
[0005] The objective of this invention is achieved through the following technical solution:
[0006] A rare earth element-doped multilayer piezoelectric sensing material, the multilayer piezoelectric sensing material comprising a stacked Gd-doped layer and a Y-doped layer;
[0007] The Gd-doped layer is composed of Pb(Mg) 1 / 3 Nb 2 / 3 O3, PbTiO3, and Gd2O3 are formed by ceramic sintering;
[0008] The Y-doped layer is composed of Pb(Mg) 1 / 3 Nb 2 / 3 O3, PbTiO3, and Y2O3 are formed by ceramic sintering.
[0009] Preferably, the Gd-doped layer is 0.71Pb(Mg) 1 / 3 Nb 2 / 3 )O3-0.29PbTiO3+1.4wt.%Gd2O3.
[0010] Preferably, the Y-doped layer is 0.71Pb(Mg) 1 / 3 Nb 2 / 3 )O3-0.29PbTiO3+1.4wt.%Y2O3.
[0011] Preferably, the Gd-doped layer and the Y-doped layer are formed by cold isostatic pressing followed by ceramic sintering.
[0012] Based on the same inventive concept, this invention also provides a method for preparing a piezoelectric sensing material, used for preparing the aforementioned rare-earth element-doped multilayer piezoelectric sensing material, the method comprising:
[0013] Preparation of precursors Nb2MgO6 and PbTiO3;
[0014] Gd-doped powder was prepared by mixing Gd2O3 with Nb2MgO6 and PbTiO3 and then grinding it.
[0015] Y₂O₃ was mixed with Nb₂MgO₆ and PbTiO₃ and then ground to obtain Y-doped layer powder.
[0016] The Gd-doped layer powder and the Y-doped layer powder are placed in layers and then pressurized to form a pre-formed piezoelectric sensing material.
[0017] The preformed piezoelectric sensing material is prepared by ceramic sintering, silver calcination, and polarization.
[0018] Preferably, the preparation of the precursors Nb₂MgO₆ and PbTiO₃ includes:
[0019] Nb2MgO6 was obtained by ball milling MgO and Ni2O5 and pre-calcining the precursor; PbTiO3 was obtained by ball milling PbO and TiO2 and pre-calcining the precursor.
[0020] Preferably, the step of obtaining Nb2MgO6 by ball milling and precursor pre-calcination of MgO and Ni2O5 includes: pre-calcining MgO and Nb2O5 at a temperature of 950℃~1000℃ for 3.5~4h to synthesize MgNb2O6.
[0021] Preferably, obtaining PbTiO3 by ball milling and precursor pre-calcination of PbO and TiO2 includes: pre-calcining PbO and TiO2 at a temperature of 780℃~800℃ for 3.5~4h to synthesize PbTiO3.
[0022] Preferably, the step of placing the Gd-doped layer powder and the Y-doped layer powder in layers and then pressing them to form a pre-formed piezoelectric sensing material includes: loading the Gd-doped layer powder into a cold isostatic pressing mold for pre-pressing; then pouring the Y-doped layer powder into a cold isostatic pressing mold and pre-pressing it again to form a double-layer stacked structure block.
[0023] Preferably, the ceramic sintering includes: a sintering temperature of 1150℃~1250℃ and a sintering time of 2~2.5h.
[0024] Preferably, the silvering process includes: a silvering temperature of 750℃~830℃ and a silvering time of not less than 30 minutes.
[0025] Preferably, the polarization includes polarizing for 30 to 36 minutes in an environment with a temperature of 80°C and a DC electric field of 1 kV / mm.
[0026] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0027] This invention provides a rare-earth element-doped multilayer piezoelectric sensing material and its preparation method to improve the sensitivity and reliability of partial discharge sensors in power equipment, thereby enhancing the accuracy of partial discharge fault detection in power equipment such as transformers. This invention employs an improved two-step solid-state reaction method. First, MgNb₂O₆ and PbTiO₄ precursors are pre-calcined. After mixing, 1.4 wt.% of Gd₂O₃ and Y₂O₃ rare-earth oxides are added respectively. A multilayer piezoelectric block is obtained by cold isostatic pressing. Sintering and polishing yield a piezoelectric sensing material with high piezoelectric coefficient and stable temperature performance. This invention also provides a general and direct method for developing high-sensitivity and high-reliability ultrasonic sensors, offering advantages such as low cost, ease of operation, and predictable results.
[0028] The piezoelectric multilayer material prepared by this invention exhibits a small change in piezoelectric coefficient below 80°C, while showing a slight decrease in piezoelectric coefficient above 80°C. This indicates that the piezoelectric coefficient of the multilayer piezoelectric material is within the normal ambient temperature range of 0-40°C. 33 Both can maintain an ultra-high voltage performance of 900 pC / N, and can maintain a high voltage performance of more than 600 pC / N even when occasionally approaching 100°C. This is because the stacked material leverages the piezoelectric performance advantages of two single rare earth doped materials. This characteristic makes the stacked material prepared in this invention suitable for use in ultrasonic sensors for partial discharge in power equipment. Attached Figure Description
[0029] Figure 1 This is a surface morphology diagram of the double-layer stacked piezoelectric ceramic material of the present invention;
[0030] Figure 2 The piezoelectric coefficient d of the 71PMN-29PT-1.4Gd, 71PMN-29PT-1.4Y, and multilayer piezoelectric materials of this invention is... 33 A graph showing how temperature changes the temperature.
[0031] Figure 3 This is a flowchart illustrating the fabrication process of the piezoelectric sensing material of the present invention. Detailed Implementation
[0032] The technical solution will be further described below with reference to the accompanying drawings and specific embodiments to help understand the content of the present invention.
[0033] Example 1
[0034] A rare earth element-doped multilayer piezoelectric sensing material, the multilayer piezoelectric sensing material comprising a stacked Gd-doped layer and a Y-doped layer;
[0035] The Gd-doped layer is composed of Pb(Mg) 1 / 3 Nb 2 / 3 O3, PbTiO3, and Gd2O3 are formed by ceramic sintering;
[0036] The Y-doped layer is composed of Pb(Mg) 1 / 3 Nb 2 / 3 O3, PbTiO3, and Y2O3 are formed by ceramic sintering.
[0037] Preferably, the Gd-doped layer is 0.71Pb(Mg) 1 / 3 Nb 2 / 3 )O3-0.29PbTiO3+1.4wt.%Gd2O3.
[0038] Preferably, the Y-doped layer is 0.71Pb(Mg) 1 / 3 Nb 2 / 3)O3-0.29PbTiO3+1.4wt.%Y2O3.
[0039] Preferably, the Gd-doped layer and the Y-doped layer are formed by cold isostatic pressing followed by ceramic sintering.
[0040] Depending on the application conditions of the sensor, the Curie temperature of the piezoelectric sensing material needs to be above 60°C and as high as possible to ensure the stability of the sensor's piezoelectric performance when the ambient temperature rises. The values disclosed in this embodiment are preferred values; the same or similar technical effects can be achieved within an acceptable fluctuation range of the component ratio, for example, a fluctuation range of ±5%. However, an excessively high or low component ratio will lead to a decrease in piezoelectric performance near the Curie temperature of that component. This invention uses an improved two-step solid-state reaction method combined with a stacking molding method to prepare a double-layer stacked piezoelectric ceramic material doped with Gd₂O₃ and Y₂O₃ rare earth oxides 71PMN-29PT. Figure 1 The image shows the surface morphology near the interlayer of the double-layer piezoelectric ceramic material. It can be seen that there are relatively clear boundaries between the different doped layers. Regardless of the type of doping, the grains shown in the images are well-grown, with clear grain boundaries, and each grain is densely grown without obvious pores.
[0041] Figure 1 Images of material surface morphology obtained using scanning electron microscopy (SEM). The abbreviations are explained below:
[0042] HV det 20.00kV ETD: This indicates that the accelerating voltage used by the high-voltage detector is 20.00 kilovolts (kV). In SEM, this voltage determines the energy of the electron beam, thus affecting the image contrast and resolution. ETD stands for "Everhart-Thornley Detector," also known as an ET Detector, a commonly used secondary electron detector. ETDs are primarily used to detect secondary electrons on the sample surface, which are ejected from the sample surface after interaction with incident high-energy electrons. In scanning electron microscopy, ETDs are used to form secondary electron images, which provide information about the sample surface morphology and composition.
[0043] Mag 1000x: This refers to the magnification, meaning the image is magnified 1000 times. This magnification allows for the observation of finer structural features on the sample surface.
[0044] WD 10.4mm: Working distance refers to the distance from the tip of the microscope objective to the sample surface. In this example, it is 10.4 millimeters (mm).
[0045] Dwell time (30μs): This refers to the length of time the electron beam remains on each pixel. A longer dwell time can improve signal strength, but it will also increase scan time. The value here is 30 microseconds (μs).
[0046] 100μm: Scale bar.
[0047] ICDR@FEIQUANTAF250: This is the instrument's identifier; FEI is the manufacturer's abbreviation; "QUANTAF250" refers to the equipment model, and "ICDR" is the analysis mode.
[0048] Before proposing this invention, the temperature characteristics of the piezoelectric coefficients of 71PMN-29PT with only Gd2O3 doping and only Y2O3 doping were tested, and the results are as follows: Figure 2 As shown. From Figure 2 As can be seen, the piezoelectric coefficient of the PMN-PT material 71PMN-29PT-1.4Gd, which is only doped with Gd2O3, shows a significant decrease when the temperature reaches 80℃. This is because the Curie temperature of this component is approximately 90℃, and the material gradually depolarizes as it approaches the Curie temperature. The piezoelectric coefficient of the PMN-PT material 71PMN-29PT-1.4Y, which is only doped with Y2O3, is relatively stable in the temperature range of 0–100℃. This is because the Curie temperature of this material is approximately 120℃, and depolarization has not yet occurred in the tested temperature range. The piezoelectric coefficient of the multilayer piezoelectric material prepared in this invention does not change much below 80℃, but decreases slightly above 80℃. This indicates that the piezoelectric coefficient of the multilayer piezoelectric material is within the normal ambient temperature range of 0–40℃. 33 Both can maintain an ultra-high voltage performance of 900 pC / N, and can maintain a high voltage performance of more than 600 pC / N even when occasionally approaching 100°C. This is because the stacked material leverages the piezoelectric performance advantages of two single rare earth doped materials. This characteristic makes the stacked material prepared in this invention suitable for use in ultrasonic sensors for partial discharge in power equipment.
[0049] This invention designs a method to dope 1.4 wt.% Gd₂O₃ and Y₂O₃ into 71PMN-29PT to prepare 0.71Pb(Mg)₂. 1 / 3Nb 2 / 3 )O3-0.29PbTiO3+1.4wt.%Gd2O3 (abbreviated as 71PMN-29PT-1.4Gd, Curie temperature approximately 92℃) and 0.71Pb(Mg 1 / 3 Nb 2 / 3A piezoelectric sensing material was designed using a composition of 0.29PbTiO3 + 1.4wt.%Y2O3 (abbreviated as 71PMN-29PT-1.4Y, Curie temperature approximately 120℃), with the composition stacked to achieve a high piezoelectric coefficient and wide temperature stability. The two layers were composed of 71PMN-29PT-1.4Gd and 71PMN-29PT-1.4Y, respectively. The stacked piezoelectric material leverages the piezoelectric advantages of both compositions (the former having a high piezoelectric coefficient, and the latter good temperature stability), achieving piezoelectric performance within the 0-40℃ range. 33 They can all maintain an ultra-high voltage electrical performance of 900pC / N, and can maintain a high voltage coefficient of over 600pC / N even at temperatures close to 100℃.
[0050] Example 2
[0051] Based on the same inventive concept, this invention also provides a method for preparing a piezoelectric sensing material, used for preparing a rare-earth element-doped multilayer piezoelectric sensing material as described in Example 1, the method comprising:
[0052] Preparation of precursors Nb2MgO6 and PbTiO3;
[0053] Gd-doped powder was prepared by mixing Gd2O3 with Nb2MgO6 and PbTiO3 and then grinding it.
[0054] Y₂O₃ was mixed with Nb₂MgO₆ and PbTiO₃ and then ground to obtain Y-doped layer powder.
[0055] The Gd-doped layer powder and the Y-doped layer powder are placed in layers and then pressurized to form a pre-formed piezoelectric sensing material.
[0056] The preformed piezoelectric sensing material is prepared by ceramic sintering, silver calcination, and polarization.
[0057] Preferably, the preparation of the precursors Nb₂MgO₆ and PbTiO₃ includes:
[0058] Nb2MgO6 was obtained by ball milling MgO and Ni2O5 and pre-calcining the precursor; PbTiO3 was obtained by ball milling PbO and TiO2 and pre-calcining the precursor.
[0059] Preferably, the step of obtaining Nb2MgO6 by ball milling and precursor pre-calcination of MgO and Ni2O5 includes: pre-calcining MgO and Nb2O5 at a temperature of 950℃~1000℃ for 3.5~4h to synthesize MgNb2O6.
[0060] Preferably, obtaining PbTiO3 by ball milling and precursor pre-calcination of PbO and TiO2 includes: pre-calcining PbO and TiO2 at a temperature of 780℃~800℃ for 3.5~4h to synthesize PbTiO3.
[0061] Preferably, the step of placing the Gd-doped layer powder and the Y-doped layer powder in layers and then pressing them to form a pre-formed piezoelectric sensing material includes: loading the Gd-doped layer powder into a cold isostatic pressing mold for pre-pressing; then pouring the Y-doped layer powder into a cold isostatic pressing mold and pre-pressing it again to form a double-layer stacked structure block.
[0062] Preferably, the ceramic sintering includes: a sintering temperature of 1150℃~1250℃ and a sintering time of 2~2.5h.
[0063] Preferably, the silvering process includes: a silvering temperature of 750℃~830℃ and a silvering time of not less than 30 minutes.
[0064] Preferably, the polarization includes polarizing for 30 to 36 minutes in an environment with a temperature of 80°C and a DC electric field of 1 kV / mm.
[0065] The purpose of this invention is to provide a rare-earth element-doped multilayer piezoelectric sensing material and its preparation method, so as to improve the sensitivity and reliability of partial discharge sensors in power equipment, and thus improve the accuracy of partial discharge fault detection in power equipment such as transformers. This invention employs an improved two-step solid-state reaction method. First, MgNb2O6 and PbTiO4 precursors are pre-calcined, then 1.4 wt.% of Gd2O3 and Y2O3 rare-earth oxides are added respectively after mixing. A multilayer piezoelectric block is obtained by cold isostatic pressing, and finally, a piezoelectric sensing material with high piezoelectric coefficient and high temperature stability is obtained through sintering and polishing. This invention provides a general and direct method for developing high-sensitivity and high-reliability ultrasonic sensors, with advantages of low cost, simple operation, and predictable results.
[0066] This invention is achieved through the following scheme:
[0067] This invention provides a piezoelectric sensing material for partial discharge sensors in power equipment, which can be fabricated through the following steps. The fabrication process is as follows: Figure 3 As shown:
[0068] (1) Composition Design: Based on the application conditions of the sensor, the Curie temperature of the piezoelectric sensing material needs to be above 60℃ and as high as possible to ensure stable piezoelectric performance when the ambient temperature rises. This invention designs the addition of 1.4 wt.% Gd₂O₃ and Y₂O₃ to 71PMN-29PT to prepare...
[0069] 0.71Pb(Mg 1 / 3 Nb2 / 3 )O3-0.29PbTiO3+1.4wt.%Gd2O3 (abbreviated as 71PMN-29PT-1.4Gd, Curie temperature approximately 92℃) and 0.71Pb(Mg 1 / 3 Nb 2 / 3 O3-0.29PbTiO3+1.4wt.%Y2O3 (abbreviated as O3-0.29PbTiO3+1.4wt.%Y2O3)
[0070] 71PMN-29PT-1.4Y (Curie temperature approximately 120°C) achieves high voltage coefficient and wide temperature stability through component stacking.
[0071] (2) Weighing: PbO, TiO2, MgO, Ni2O5, Gd2O3 and Y2O3 are selected as raw materials. The weight of each component is calculated according to the stoichiometric ratio and weighed. The purity of each raw material is higher than 99%. Weighing should be done in one weighing as much as possible. Multiple weighings should be avoided to prevent the accumulation of errors. The weighing error should not exceed 0.010g.
[0072] (3) First ball milling: The grinding balls for the first ball milling are agate balls of different sizes. Before grinding the raw materials, to ensure that the grinding jar is clean and free of impurities, pure water should be added first and the ball milling should be completed until the liquid is clear. Then, alcohol should be added and the ball milling should be completed for half an hour. The grinding jars should be numbered in advance. Then, the mixed raw materials of MgO and Ni2O5 are placed in the jar numbered 1, and the mixed raw materials of PbO and TiO2 are placed in the jar numbered 2. About 1 / 3 volume of anhydrous ethanol is poured into each jar to slightly submerge the sample.
[0073] The ball milling speed here is 600 r / min, and the time is 6 hours.
[0074] (4) First drying: Pour the ball-ground sample into a petri dish, cover the petri dish with filter paper, and put it in an oven to dry for about 5 hours until the alcohol evaporates and the sample surface cracks.
[0075] (5) Precursor pre-calcination: Pour the dried powder into a mortar and grind it into a fine powder, then press it into a small crucible. Place a zirconium plate in the box furnace, then place the crucible, and finally cover it with the zirconium plate. Place the two mixtures separately into the box furnace for pre-calcination.
[0076] MgO and Nb₂O₅ were pre-calcined at 950℃ for 4 hours to synthesize MgNb₂O₆, while PbO and TiO₂ were also...
[0077] PbTiO3 was synthesized by pre-calcination at 780℃ for 4 hours.
[0078] (6) Weighing: Crush the pre-fired ceramic sample and re-grind it into fine powder. Mix MgNb2O6 and PbTiO3, and add Gd2O3 and Y2O3 according to the stoichiometric ratio to the mixture. The ball mill jars are numbered 3 and 4.
[0079] (7) Secondary ball milling: Replace the agate balls with alumina ball milling beads of the same size, and then use wet ball milling again to process the mixture containing different rare earth oxides. The secondary ball milling speed is 600 r / min and the time is 24 h.
[0080] (8) Secondary drying: Pour the ball-ground sample into a petri dish, cover the petri dish with filter paper, and put it in an oven to dry for about 5 hours until the alcohol evaporates and the sample surface cracks.
[0081] (9) Pre-compression: First, pour the dried powder into a mortar and grind it into a fine powder. Then, put 0.5g of powder doped with Gd2O3 into a cold isostatic pressing mold and pre-compress it for 1 minute at 10MPa using a tablet press. Next, pour 0.5g of powder doped with Y2O3 into the mold and pre-compress it for 1 minute at 10MPa using a tablet press to initially form a double-layered structure block with different compositions. Then, demold the layered material and pack it into a latex bag and arrange them in sequence. A certain space should be left between the formed samples. Then, vacuum the latex bag.
[0082] (10) Cold isostatic pressing: After sealing the vacuum latex bag, put it into a cold isostatic press and press it for 3 minutes under 200MPa hydraulic pressure. Such samples are more dense than those prepared by dry pressing.
[0083] (11) Sintering: The pressed cylindrical sample was sintered in a box furnace by embedding. The sintering temperature was 1225℃ and the sintering time was 2 hours to obtain a double-layer piezoelectric material with the composition of 71PMN-29PT-1.4Gd and 71PMN-29PT-1.4Y.
[0084] (12) Machining: The piezoelectric ceramic is machined by external cylindrical and surface grinding machines to obtain a smooth and flat ultrasonic core material with a diameter of 10cm.
[0085] (13) Silver coating: Take the processed cylindrical sample, coat it evenly with silver paste diluted with turpentine, and repeat three times after drying to ensure the smoothness and integrity of the silver layer.
[0086] (14) Silver burning: Place the dried sample into a box furnace and heat it again. The silver burning temperature is 800℃ and the time is 30 minutes. Polarization: After the silver burning, the sample is polarized for 30 minutes at 80℃ and a DC electric field of 1kV / mm.
[0087] Examples 3-6
[0088] The specific implementation method is the same as that in Example 2, with the differences shown in Table 1 below:
[0089] Table 1 shows the differences in some preparation conditions.
[0090]
[0091]
[0092] The performance of the piezoelectric sensing materials obtained in Examples 3-6 is comparable to that of the piezoelectric sensing materials in Example 1 or Example 2, and the technical effects are the same.
[0093] This invention employs an improved two-step solid-state reaction method, which successfully prepares 71PMN-29PT relaxor ferroelectric ceramics doped with rare earth oxides with high piezoelectric properties. This method effectively suppresses the formation of harmful impurity phases such as pyrochlore, ensuring the piezoelectric properties of the material. At the same time, this method is inexpensive and does not require complicated processes, making it particularly suitable for industrial production.
[0094] This invention employs a cold isostatic pressing process for forming piezoelectric ceramics, which results in a denser sample compared to that obtained by dry pressing, ensuring that the laminated material possesses higher piezoelectric properties.
[0095] The above are merely embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention are included within the scope of the claims of the present invention.
Claims
1. A rare-earth element-doped multilayer piezoelectric sensing material, characterized in that, The stacked piezoelectric sensing material includes a stacked Gd-doped layer and a Y-doped layer; The Gd-doped layer is composed of Pb(Mg) 1 / 3 Nb 2 / 3 O3, PbTiO3, and Gd2O3 are formed by ceramic sintering; The Y-doped layer is composed of Pb(Mg) 1 / 3 Nb 2 / 3 O3, PbTiO3, and Y2O3 are formed by ceramic sintering; The Gd-doped layer is 0.71Pb(Mg) 1 / 3 Nb 2 / 3 )O3-0.29PbTiO3+1.4wt.%Gd2O3; The Y-doped layer is 0.71Pb(Mg) 1 / 3 Nb 2 / 3 )O3- 0.29PbTiO3+1.4wt.% Y2O3.
2. The rare-earth element-doped multilayer piezoelectric sensing material as described in claim 1, characterized in that, The Gd-doped layer and Y-doped layer are formed by cold isostatic pressing followed by ceramic sintering.
3. A method for preparing a piezoelectric sensing material, characterized in that, The method for preparing a rare-earth element-doped multilayer piezoelectric sensing material as described in claim 1 or 2 includes: Preparation of precursors Nb2MgO6 and PbTiO3; Gd-doped powder was prepared by mixing Gd2O3 with Nb2MgO6 and PbTiO3 and then grinding it. Y₂O₃ was mixed with Nb₂MgO₆ and PbTiO₃ and then ground to obtain Y-doped layer powder. The Gd-doped layer powder and the Y-doped layer powder are placed in layers and then pressurized to form a pre-formed piezoelectric sensing material. The preformed piezoelectric sensing material is prepared by ceramic sintering, silver calcination, and polarization to obtain the piezoelectric sensing material. The Gd-doped layer is 0.71Pb(Mg) 1 / 3 Nb 2 / 3 )O3-0.29PbTiO3+1.4wt.%Gd2O3; The Y-doped layer is 0.71Pb(Mg) 1 / 3 Nb 2 / 3 )O3- 0.29PbTiO3+1.4wt.% Y2O3.
4. The method for preparing a piezoelectric sensing material as described in claim 3, characterized in that, The preparation of the precursors Nb₂MgO₆ and PbTiO₃ includes: Nb2MgO6 was obtained by ball milling MgO and Ni2O5 and pre-calcining the precursor. PbTiO3 was obtained by ball milling PbO and TiO2 and pre-calcining the precursor.
5. The method for preparing a piezoelectric sensing material as described in claim 4, characterized in that, The process of obtaining Nb2MgO6 by ball milling and precursor pre-calcination of MgO and Ni2O5 includes: pre-calcining MgO and Nb2O5 at a temperature of 950℃~1000℃ for 3.5~4h to synthesize Nb2MgO6.
6. The method for preparing a piezoelectric sensing material as described in claim 4, characterized in that, The process of obtaining PbTiO3 by ball milling and precursor pre-calcination of PbO and TiO2 includes: pre-calcining PbO and TiO2 at a temperature of 780℃~800℃ for 3.5~4h to synthesize PbTiO3.
7. The method for preparing a piezoelectric sensing material as described in claim 3, characterized in that, The step of placing the Gd-doped powder and the Y-doped powder in layers and then pressing them together to form a pre-formed piezoelectric sensing material includes: loading the Gd-doped powder into a cold isostatic pressing mold for pre-pressing; then pouring the Y-doped powder into a cold isostatic pressing mold and pre-pressing it again to form a double-layer stacked structure block.
8. The method for preparing a piezoelectric sensing material as described in claim 3, characterized in that, The ceramic sintering includes: a sintering temperature of 1150℃~1250℃ and a sintering time of 2~2.5h.
9. The method for preparing a piezoelectric sensing material as described in claim 3, characterized in that, The silver-burning process includes: a silver-burning temperature of 750℃~830℃ and a time of not less than 30 minutes.
10. The method for preparing a piezoelectric sensing material as described in claim 3, characterized in that, The polarization includes polarizing for 30-36 minutes in an environment with a temperature of 80°C and a DC electric field of 1kV / mm.
Citation Information
Patent Citations
Graded-distribution ferroelectric phase change type lead magnesio-niobate-lead titanate ceramic material
CN101948311A
Preparation method of lanthanum-doped lead magnesioniobate-lead titanate transparent ceramic
CN104072136A